Better to Own or to Regulate? The Case of Alcohol Distribution and Sales. (February 2017) - Zullo, Roland
Alcohol-related income generation is compared across monopoly and license off-premise alcohol regulatory models in U.S. states, 1977-2010. An optimum organizational-ownership mix is found when states directly own alcohol wholesale and employ a network of state-owned retailers serving urban regions and private agents serving less-populated regions. Per capita alcohol-related income in US dollars for these optimal systems was 58.82 compared with 26.72 with license systems. This disparity held after controlling for alcohol sales and retail hours of operation. The findings challenge the wisdom of asset divestment as a response to fiscal stress and contradict a central tenet of New Public Management (NPM) Theory.